Faktor-Faktor Yang Mempengaruhi Permintaan Cabai Merah di Kota Kediri - Kalam Mahardika Achmad; Ririt Iriani S (Peneliti.net, 2023)
Chili cultivation is the largest vegetable cultivation cultivated by farmers in Indonesia. The increasing need for chili is in line with population growth and the development of processed chili products. Fluctuations in commodity prices can affect the amount of commodity demand that exists. This study aimed to analyze how much influence the price of chili, the price of shallots, and the number of residents on the demand in Kediri City. This type of research is included in quantitative descriptive research. IBM SPSS (Statistical Package for Social Science) Version 25 was used for analytical tools in this study. This research data was collected from the Central Statistics Agency of Kediri City between 2011 and 2021, the Pasa Monitoring System and Basic Needs of the Ministry of Trade between 2015 and 2021 and the Kediri City Agriculture Office, between 2011 and 2021. Based on this study, the price of shallots (X2) did not significantly influence Kediri City. While the price of red chili (X1) has a significant influence on the demand for red pepper in Kediri City, the number of residents (X3) has a significant effect.